A utilização dos isótopos estáveis (δ13C e δ15N) na contribuição das fontes de carbono e posição trófica de Plagioscion squamosissimus e Hypophthalmus edentatus, na planície de inundação do alto rio Paraná. - Manetta, Gislaine Iachstel (2006)
The present study (1) investigates the δ13C and δ15N isotopic composition in frozen samples (control), samples in alcohol and in formaldehyde (2) identify intraspecific variations in isotope values during the stages of larval development, and (3)estimate the trophic positions based on food intake (diet) and assimilation (δ15N) and (4) analyzes, using δ13C, if the primary producer assimilated continues being the same one required by the juvenile and adults Plagioscion squamosissimus (Sciaenidae) and Hypophthalmus edentatus (Hypophthalmidae). The monthly samplings were concentrated during the spawning season of the species, in the Ivinheima River, located in the Upper Paraná River floodplain and adults on the Parana River. From each individual we extracted a strip of muscle from the region above the lateral line, in the dorsal fin base, that was divided into three equal parts, each one was submitted to one type of treatment: freeze (-15oC), conservation in alcohol 70% and fixation in formaldehyde 4%. The specimens were grouped, according to level of notochord development, into: preflexion, flexion and postflexion stages. Afterwards, they were dried up in air oven at 60oC for 48 hours and macerated until the obtaining of a fine powder and sent to the determination isotopic. Trophic positions were estimated based on the isotope value of nitrogen (PTδ15N) and from the diet (PTMd). The carbon isotopic values of samples in alcohol were mostly enriched compared to control, whereas the samples in formaldehyde presented depleted values. The nitrogen isotopic values for both samples preserved in alcohol and formaldehyde were enriched when compared to the values of frozen samples, independently of used preservatives. During the different stages of development, only for P. squamosissimus, there were significant differences in the isotope values of δ15N. The trophic positions calculated based on diet composition (PTMd) occupied the same trophic level (third) of PTδ15N, during the developmental stages. The order of the contributions of the primary sources for the species was identified phytoplankton, riparian vegetation, C3 macrophytes, periphyton and C4 macrophyte. Thus, in order to keep the main primary producers, the human interventions that affect phytoplankton community and structure of riparian vegetation should be minimized.